Pemahaman Mahasiswa Pendidikan Biologi Terhadap Pentingnya Penggunaan Tabir Surya - Camelia, Shafa Tasya; Zahro, Risa Dhotus; Meithasari, Yessi; Tauhidah, Dian (Biosel Biology Science and Education, 2020)
Prolonged exposure to direct sunlight can cause various health problems. Sunscreen can prevent the entry of direct sunlight into the skin, but there are still many people who are unfamiliar about the importance of using sunscreen. This research was conducted to determine student understanding of the importance of using sunscreen. This research was a survey research conducted at Biology Education UIN Walisongo Semarang from various forces. The research instrument was a questionnaire. The results showed that students already understood the importance of sunscreen, but they preferred to wear closed clothing rather than using sunscreen. Keywords: Sun Screen, Undergraduate Students, Survey